Efeito da adubação nitrogenada na produtividade do girassol - Lobo, Thomaz Figueiredo [UNESP]; Grassi Filho, Helio [UNESP]; Coelho, Hugo Alexandre [UNESP] (My University, 2012)
Nitrogen, along with K, is the most limiting nutrient for sunflower productivity. The objective of this research work was to determine the best level of nitrogen in a fertilization formula for the cultivation of sunflower of the ‘HELIO – 251’ cultivar. The fertilization procedure was that recommended for the state of São Paulo for sunflower crop, except that, in each one of the treatments, N doses were of 50, 70, 90, 110, and 130 kg ha-1 . These treatments were distributed in the field according to a randomized complete block design with 4 replications. The N dose which resulted in the highest grain yield, highest oil content, and plant dry matter was of 100 kg ha-1 . Leaf N content and 1,000 grains weight increased with N doses.

O nitrogênio (N) juntamente com o potássio (K) é o nutriente que mais limita a produção do girassol. O objetivo do trabalho foi avaliar a melhor dose de N para a cultivar de girassol HELIO – 251. Adotou- -se a adubação de acordo com a recomendação de adubação para o Estado de São Paulo para todos os tratamentos, com variação somente da adubação nitrogenada configurando um delineamento experimental em blocos casualizados constituído por 5 tratamentos e 4 repetições. Os tratamentos foram: 50 kg ha-1 de N; 70 kg ha-1 de N; 90 kg ha-1 de N; 110 kg ha-1 de N; 130 kg ha-1 de N, foram utilizados como fonte de N a uréia. A melhor dosagem de N para a produtividade de grãos, de óleo e de matéria seca do girassol foi de 100 kg ha-1 . O teor de N foliar e o peso de mil grãos aumentaram em função do aumento da dose de N.
Effect of nitrogen fertilization on yield of sunflower
Keywords: Helianthus annuus L.; Yield; Nitrogen efficiency; Helianthus annuus L.; Rendimento; Eficiência do nitrogênio